Investigating the Role of Dermatoglyphics In Multiple Intelligence – a Case Study: Dermatoglyphics and its Impact on Human Intelligence (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This research aims to confirm that humanbeings possess unique blend of intelligences. Human intelligence and Dermatoglyphics,both are influenced by genetic factors. The aim of this paper is to relate Dermatoglyphicsand human intelligence in young individuals pursuing graduation. Findings ofthis research revealed that the Dermatoglyphics, ADRC (Asian DermatoglyphicsResearch Centre) as a scientific discipline, DMIT is a remarkable offshoot ofHoward Gardner's Theory of Multiple Intelligences which has the followingsalient features: Overview of the Dermatoglyphics and the Dermatoglyphics MultipleIntelligence Test/Analysis; Personality Assessment; Profile based on Gardner's MultipleIntelligences and Learning Styles, Strength of Congenital Abilities, WorkingStyle, Leadership Style, Management Style; Report Interpretation; andCustomized Academic and Relationship Advises; the respondents of this studygave their perceptions to the beneficial results of the DMIT; and the foregoingfindings have some implications that may be used by academic institutions andindividuals to enhance their life and make it more successful.